Advanced control structures for induction motors with ideal current loop response using field oriented control - Ha, Vo Thanh; Lam, Nguyen Tung; Ha, Vo Thu; Vinh, Vo Quang (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Field oriented control (FOC) is widely used for high performance induction motor (IM) electrical drive systems. Typically, FOC uses linear controls and space vector modulation (SVM) to control the fundamental components of the stator voltages. This work shows that based on a fast and precise inner current loop response one may flexibly employ different advanced control methods, to achieve high performance outer loops (speed and flux control). In this paper, novel approaches based on dead-beat scheme for the current loop combining with exact linearization, backstepping controls, and fatness-based methods for the outer loop are proposed. By comparing with classical PI control, the proposed method shows the outstanding features of system response such as fast, accurate and decoupling properties. The performance evaluation is given by experimental results.